2010
DOI: 10.1007/s00520-010-0916-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life after radical prostatectomy in wives of men in the postoperative adjuvant androgen deprivation trial

Abstract: Purpose We examined quality of life in spouses of men in the Post-Adjuvant Androgen Deprivation trial after radical prostatectomy. Methods Men at high risk of prostate cancer recurrence were randomized to receive androgen deprivation therapy or observation. Forty-three couples completed telephone interviews every 6 months for 2 years assessing women’s mood disturbance, mental and physical health, and sexual function and bother as well as men’s symptoms and sociodemographic and marital variables. We used line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Another study showed that not only female cancer patients, but also female partners of male cancer patients, perceived more psychological distress and a lower quality of life than women in healthy couples, although male partners of female cancer patients did not differ from their healthy controls [ 9 ]. For example, spouses of prostate cancer patients suffered conditions affecting their mood, mental and physical health, and sexual function [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that not only female cancer patients, but also female partners of male cancer patients, perceived more psychological distress and a lower quality of life than women in healthy couples, although male partners of female cancer patients did not differ from their healthy controls [ 9 ]. For example, spouses of prostate cancer patients suffered conditions affecting their mood, mental and physical health, and sexual function [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were role and gender differences regarding psychological distress and quality of life when dealing with cancer. Not only female cancer patients, but also female partners of male cancer patients, had psychological distress and a low quality of life [ 9 , 10 ]. In addition, female cancer patients seem to suffer different types of distress compared with male patients.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Of the few longitudinal studies in this context that exceed 1-year follow-up, most considered general or disease-specific QoL, 9,14 and where psychological outcomes were assessed, few applied validated measures of distress. Sterba et al 15 found that partners' of men treated with radical prostatectomy and receiving postadjuvant treatment or observation had improved mental health over the 24-month study period. 15 However, this study was limited by including only 31 partners, and so an understanding of long-term partners' psychological distress is a knowledge gap.…”
Section: Introductionmentioning
confidence: 99%
“…Sterba et al 15 found that partners' of men treated with radical prostatectomy and receiving postadjuvant treatment or observation had improved mental health over the 24-month study period. 15 However, this study was limited by including only 31 partners, and so an understanding of long-term partners' psychological distress is a knowledge gap. In addition, there remains a lack of clarity about prospective and potentially modifiable predictors of distress.…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining psychological functioning in PC patients and their spouses, Eton and colleagues (Eton et al, 2005) found that spouses were more likely than patients to report cancer-specific distress, including more avoidance and intrusive thoughts. Spouses report distress associated with the demands of caregiving for a cancer patient (Northouse et al, 2007a; Sterba et al, 2010), the threat of losing a loved one (Eton et al, 2005; Northouse et al, 2007b), and social isolation (Carter et al, 2010; Williamson et al, 1998). …”
Section: Introductionmentioning
confidence: 99%